Upaya Guru Dalam Menerapkan Nilai-Nilai Moderasi Beragama Dalam Pembelajaran PAI di SMAN 3 Purwakarta - Pransah, Muhamad Dika; Hilmi, Ahmad Ariffudin; Solehudin, Azis; Maulana, Khaidir (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
SMAN 3 Purwakarta is a public high school with a diverse student body, making it vulnerable to the influence of extreme ideologies. In this context, the role of Islamic Education (PAI) teachers is crucial in instilling the values of religious moderation. This study aims to: (1) understand the approaches and methods used by PAI teachers in fostering religious moderation values, and (2) identify the supporting and inhibiting factors in this process. This research employs a descriptive qualitative approach, with subjects including three PAI teachers, the Vice Principal for Curriculum, and five upper-grade students. Data were collected through observation, interviews, and documentation, then analyzed using data collection, reduction, presentation, and conclusion drawing.Findings indicate that religious moderation is instilled through two approaches: (1) direct educational processes, including internalizing values through guidance, advice, and motivation to uphold tolerance and good morals; and (2) indirect educational processes, such as prevention, mitigation, regulations, and sanctions to maintain a peaceful and harmonious school environment. Methods used include (a) giving advice, (b) setting a good example, (c) discipline, (d) punishment, (e) habituation, and (f) providing special attention. Supporting factors include (a) alignment of orientations between PAI teachers and other teachers, (b) supportive school policies, (c) parental support, and (d) the role of social media. Inhibiting factors include (a) lack of facilities and teachers for non-Muslim students, (b) low student interest in learning, (c) difficulty in managing students, and (d) students' lack of attention.